ENDOMETRIAL HYPERPLASIA IN OBESE PATIENTS OF REPRODUCTIVE AGE PRESENTED WITH ABNORMAL UTERINE BLEEDING.: JPUMHS;2024:14:04,87-93. http://doi.org/10.46536/jpumhs/2024/14.04.564 - Ayesha Nasir1, Sanum Sultana Khattak2, Heema3, Rubab Ahmad4, Mohammad Tahir5, Maryam Zahra6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
BACKGROUNG: Abnormal uterine bleeding AUB is commonly reported at the gynecological OPDs as approximately 1 in every 3 patients in these OPDs reports about this complaint OBJECTIVES: This Study aimed to determine the frequency of endometrial hyperplasia in obese patients of reproductive age with abnormal uterine bleeding. METHODS: This cross sectional study was carried from 1st of March 2023 to 31st July 2023 at the Department of Gynaecology and Obstetrics District Head Quarter Hospital, Mardan. A total of 213 women between the ages of 18-40 years with BMI≥ 30 kg/m2 with complaint of abnormal uterine bleeding were included in this study. Endometrial thickness was assessed through transvaginal ultrasonography. Endometrial hyperplasia was diagnosed when ultrasonography showed quite 7 mm thickness of endometrium within two days after the end of menstruation. Statistical analysis was done using IBM SPSS Version 25. RESULTS: The Mean age was 29.36±6.52 years, range from of 18-40 years. The mean BMI was 32.83±2.27 while mean parity was 1.73±1.26. Results of transvaginal ultrasonography show the presence of endometrial hyperplasia in 13.15% of these obese women. BMI stratification ratio showed higher in patients endometrial hyperplasia BMI≥35 than patients with BMI˂35 although the difference was not statistically significant. CONCLUSION: The obese women consulting for abnormal uterine bleeding in their reproductive age have a considerable risk for the development of endometrial hyperplasia and must be assessed for its diagnosis.